iREFLECT v1: embracing technology to get learners’ reflective formative feedback after face-to-face class / Nur Farah Fadhliah Mahmud, Noor Fadhleen Mahmud and Siti Huzaimah Sahari - Mahmud, Nur Farah Fadhliah; Mahmud, Mahmud; Sahari, Siti Huzaimah (Universiti Teknologi MARA, Kedah, 2023)
The new age of teaching has been witnessing the evolving of technology utilized by instructors to enhance learning experience for their students. Asking students to reflect their learning using online written communication after each class i.e., formative feedback is seen to be an effective way to improve learners’ learning in an academic classroom setting. By using iREFLECT v1, it is easier for the students to provide feedback based on what they have learned after each faceto- face class. Not only students, but instructors may also gain benefits by obtaining faster response and enabling the process of teaching and learning to become comprehensive and exciting – which make teaching and learning more comprehensive. This iREFLECT v1 contains several questions which will assist instructors to develop students’ profiling and students’ preference in learning. iREFLECT v1 is a template that includes a set of questions consisting of students' profile, feelings (on that day), readiness for the class, understanding about the topic of the day and their suggestions for their next class. iREFLECT v1 will assist instructors to get fast feedback from the students, thus can enhance teaching and learning experience in an academic classroom setting.